Penyediaan Air Bersih Masyarakat Sekitar Masjid Al-Iklas Desa Cukanggenteng Ciwidey dengan Menggunakan Penyaringan Air Sederhana - Hans Kristianto; Katherine Katherine; Jenny N. M. Soetedjo (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2017)
Cukanggenteng Village, Ciwidey, Bandung has problem with availability of clean water. The villagers use water from Cisondari River near the village and shallow well which has high turbidity. Usage of high turbidity water could cause various health problems, such as cholera, dysentery, typhus, and so on. There is some effort done by the villager to reduce the water turbidity, by utilizing sedimentation process. However the sedimentation process does not work effectively. In this community service project, a sand filter and pipe filter was utilized to solve the clean water scarcity problem. The sand filter was operated up flow, and its overflow was fed into the pipe filter. The pipe filter consisted of three 4” pipes with sand, coconut shell carbon, and sponge. This system was designed with easily obtained filter media, and simple construction, so that it could be taken care, operated, duplicated by the villagers. Analysis of the water showed that the filtration could remove 91.06% of water turbidity from 94.55 NTU to 8.445 NTU, with pH 6.55. The water after this simple filtration process could be categorized as clean water, based on the standards in PERMENKES RI No. 416/MENKES/PER/IX/1990. The results obtained showed that the filtration process has successfully implemented to reduce the water turbidity.